Biological characterization of adult MYC-translocation-positive mature B-cell lymphomas other than molecular Burkitt lymphoma. - Aukema, S. M.; Kreuz, M.; Kohler, C. W.; Rosolowski, M.; Hasenclever, D.; Hummel, M.; Kuppers, R.; Lenze, D.; Ott, G.; Pott, C.; Richter, J.; Rosenwald, A.; et al. (Haematologica, 2014)
Chromosomal translocations affecting the MYC oncogene are the biological hallmark of Burkitt lymphomas but also occur in a subset of other mature B-cell lymphomas. If accompanied by a chromosomal break targeting the BCL2 and/or BCL6 oncogene these MYC translocation-positive (MYC(+)) lymphomas are called double-hit lymphomas, otherwise the term single-hit lymphomas is applied. In order to characterize the biological features of these MYC(+) lymphomas other than Burkitt lymphoma we explored, after exclusion of molecular Burkitt lymphoma as defined by gene expression profiling, the molecular, pathological and clinical aspects of 80 MYC-translocation-positive lymphomas (31 single-hit, 46 double-hit and 3 MYC(+)-lymphomas with unknown BCL6 status). Comparison of single-hit and double-hit lymphomas revealed no difference in MYC partner (IG/non-IG), genomic complexity, MYC expression or gene expression profile. Double-hit lymphomas more frequently showed a germinal center B-cell-like gene expression profile and had higher IGH and MYC mutation frequencies. Gene expression profiling revealed 130 differentially expressed genes between BCL6(+)/MYC(+) and BCL2(+)/MYC(+) double-hit lymphomas. BCL2(+)/MYC(+) double-hit lymphomas more frequently showed a germinal center B-like gene expression profile. Analysis of all lymphomas according to MYC partner (IG/non-IG) revealed no substantial differences. In this series of lymphomas, in which immunochemotherapy was administered in only a minority of cases, single-hit and double-hit lymphomas had a similar poor outcome in contrast to the outcome of molecular Burkitt lymphoma and lymphomas without the MYC break. Our data suggest that, after excluding molecular Burkitt lymphoma and pediatric cases, MYC(+) lymphomas are biologically quite homogeneous with single-hit and double-hit lymphomas as well as IG-MYC and non-IG-MYC(+) lymphomas sharing various molecular characteristics.
Keywords: Adult; Aged; Aged, 80 and over; Burkitt Lymphoma/diagnosis/*genetics/metabolism/mortality; Cluster Analysis; Female; Gene Expression Regulation, Neoplastic; *Genes, myc; Genomics; Humans; Immunoglobulin Heavy Chains/genetics; Lymphoma, B-Cell/diagnosis/*genetics/metabolism/mortality; Male; Middle Aged; Neoplasm Grading; Oncogene Proteins, Fusion; Proto-Oncogene Proteins c-bcl-2/genetics; Proto-Oncogene Proteins c-bcl-6/genetics; Transcriptome; *Translocation, Genetic